Hvilket Norge i hvilket Europa? - Erik Fossum, John; Trondal, Jarle; Aurvåg Farsund, Arild; Dotterud Leiren, Merethe; Melchior, Arne; Riddervold, Marianne; Rieker, Pernille; Døhlie Saltnes, Johanne; Sverdrup, Ulf (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2025)
Contending with significant democratic and security policy risks and challenges, Europe is in a state of considerable turbulence. Current discourse about Europe's future must be seen in light of deep uncertainty about the direction in which it is heading. In Norway, we face many of the same challenges, and in this book we ask ourselves how Norway's development and future are influenced by Europe's. The book therefore discusses different scenarios for the development of the most important organization in Europe, the European Union (EU), and possible effects the different scenarios may have on Norwegian politics and society. The book outlines three broad scenarios that are explored further within a number of policy areas: economic security, climate policy, agricultural policy, foreign security and defense policy, trade and development policy. The book's agenda is thus comprehensive, broader in scope than a slim anthology can accommodate. It is intended not only as a scholarly analysis of Norway and the EU, but also as a contribution to the Norwegian debate about Europe and what might shape its further development. Which Norway in Which Europe? will be of interest to students of European politics as well as the general public. ;Europa står i betydelig turbulens, med store demokratiske og sikkerhetspolitiske risikoer og utfordringer. Debatten om hvilket Europa man ønsker må ses i lys av betydelig usikkerhet om hvilken retning Europa beveger seg i. I Norge møter vi mange av de samme utfordringene, og vi spør oss i denne boken hvordan Norges utvikling og fremtid påvirkes av Europas. Boken diskuterer derfor ulike scenarioer for utviklingen av den viktigste organisasjonen i Europa, Den europeiske union (EU), og hvilke effekter de ulike scenarioene vil ha for norsk politikk og samfunn. I boken trekkes det opp tre brede scenarioer, som videre diskuteres innenfor en rekke politikkområder: økonomisk sikkerhet, klimapolitikk, landbrukspolitikk, utenriks-, sikkerhets- og forsvarspolitikk, handelspolitikk, og utviklingspolitikk. Dagsordenen for boken er derfor omfattende, og større enn en liten bok kan romme. Boken er tenkt ikke bare som en fagbok om Norge og EU, men også som et innspill til den norske europadebatten og til vurderingen av hva som kan prege Europas videre utvikling. Hvilket Norge i hvilket Europa? er relevant for studenter i europastudier samt den interesserte offentlighet.